Body Mass Index (BMI) Is Up, but Not Significantly in College-Aged Young Adults During the COVID-19 Pandemic. (14th June 2022) - Parker, Kelly; Rhee, Yeong
Abstract: Objectives: It has been suggested that the pandemic has contributed to weight gain in the general population. Increased weight is associated with health problems such as cardiovascular disease and diabetes. This study examined whether BMI changed over the course of the COVID-19 pandemic in a sample of college-aged young adults. Methods: College-aged young adults completed a survey wherein they self-reported their height (in inches) and weight (in pounds). This survey was conducted at two time points during the COVID-19 pandemic, in the Spring of 2020 and in the Fall of 2021. These data were used to calculate Body Mass Index (BMI) and the year of entry was coded. Independent t-tests were used to measure differences between years of the study. Results are reported as mean ± standard deviation. Results: During year 1, 146 of 196 respondents reported height and weight. For year 2, 128 of 143 respondents reported height and weight. The average BMI during year 1 of the study was 24.80 ± 5.12 kg/m 2 . This result creeped up to 25.03 ± 5.68 kg/m 2 during year 2 of the study. However, the increase in BMI was not significant ( p  = 0.73). During both study years, the majority of respondents were of healthy weight, according to BMI classifications with 5 participants classified as underweight, 80 classified as healthy weight, and 63 classified as overweight or obese in year 1. In year 2, 9 participants were classified as underweight, 77 were classified as healthy weight, and 50 were classified as overweight or obese. Conclusions: The proportion of participants classified as overweight or obese in our sample was less than the United States' national level of 73.6%. Numerous factors may have contributed to the maintenance of BMI status in this age group during the pandemic, including youthful age, diet or activity changes, or differences in stress, work status, and familial responsibilities. While the BMI change was not significant, an increase in the number of underweight participants (3% to 7%), in addition to the overall upward BMI trend suggests that an increased focus on and awareness of healthy diets and physical activity as a means of managing stress may improve overall physical and mental wellbeing in this age group. Funding Sources: Not applicable.